Diabetic kidney disease: Is there a non-albuminuric phenotype in type 2 diabetic patients? - Ivo Laranjinha; Patrícia Matias; Sofia Mateus; Filipa Aguiar; Patrícia Pereira; Miguel Perneta Santos; Rui Costa; Ana Lourenço; José Guia; José Diogo Barata; Luís Campos (Nefrología, 2016)
Background: Albuminuria was widely considered as the first clinical sign of diabetic kidney disease (DKD), which is why it has traditionally been used as a screening test for DKD. However, increasing evidence has shown that a significant number of type 2 diabetes mellitus (DM) patients have a decreased glomerular filtration rate (GFR) without significant albuminuria, known as non-albuminuric DKD (NA-DKD). The aim of this study was to determine the prevalence and the demographic and clinical characteristics of patients with NA-DKD. Methods: This was a 1-year retrospective study that included 146 type 2 diabetic patients with GFR < 75 mL/min followed-up in a diabetes outpatient department. Patients were divided into two groups according to their ACR status – NA-DKD and albuminuric DKD (A-DKD). Results: Of the 146 patients included in the study, 53.4% had A-DKD and 46.6% had NA-DKD. According to the multivariable analysis performed, patients with NA-DKD tended to be older (p = 0.021), female (p = 0.045) and with a lower GFR (p = 0.004) than A-DKD patients. There was no difference between the groups in terms of body mass index, metabolic control of DM, duration of DM diagnosis and prevalence of metabolic syndrome. Conclusions: The majority of patients with DKD had albuminuria, but a significant proportion had a non-albuminuric phenotype (46.6% in this population). These patients exhibit distinct clinical features that could have screening, therapeutic and prognosis implications.